Building Up Brand Loyalty Through Customer Experience of CV Araya Putra - Zahiro, Wirda Aini; Muslih, Basthoumi (Universitas Nusantara PGRI Kediri, 2025)
Research aim : This research aims to explore the influence of customer experience on brand loyalty at CV Araya Putra, a company operating in the horticulture sector. Using a qualitative approach and case study methods, this research seeks to understand how elements of customer experience, such as interactions with services, product quality, and emotional value, can contribute to the formation of customer loyalty. Design/Method/Approach : This research is a qualitative approach with a case study method. Informants were selected based on various criteria (relevance, recommendation, readiness, and reassurance). The research informants in this research were CV Araya Putra customers who had used the product or service. The interview was conducted using an interview guide technique which consists of open questions that discuss various dimensions of customer experience such as product quality, service, emotional connection, and other factors that influence their decision to remain loyal to the brand. By using data validity, triangulation of data sources to ensure the accuracy of the information. Research Finding : The data shown that customer a highly values product quality and responsive customer service, which creates an emotional bond with the brand and the ease of use of the e-commerce platform. The key elements of the customer experience not only product quality, but also quality of staff service, shopping convenience in the store, navigation on the website, and product delivery. The strategy that can be implemented by CV Araya Putra to increase their customer loyalty that combine cognitive (product quality) and emotional (relationship with the brand) satisfaction.. Theoretical contribution/Originality : This research provides strategic recommendations for CV Araya Putra, including improving customer service, optimizing customer experience on digital platforms, and developing stronger emotional relationships with customers. Practitionel/Policy implication : This study not only provides insight for companies in increasing brand loyalty, but also contributes to the academic literature regarding the relationship between customer experience and brand loyalty in the field of horticulture. Research limitation : Several obstacles were also found, such as inconsistency in service and lack of use of customer feedback for quality improvement.